Football, Conservative Values, and a Feeling of Oneness with the Group: A Study of Polish Football Fandom. Issue 4 (November 2018) - Kossakowski, Radosław; Besta, Tomasz
The main aim of this article is to show some characteristics of the identity of Polish football supporters. The results of a study conducted among 309 fans actively engaged in formal (supporters' associations) and informal groups (e.g., hooligans or ultras), as well as data from qualitative research, reveal their strong identification with Poland as a country, with their family, club, and group of supporters. At the same time, Polish fans do not identify with "Europe" as a category. The fandom culture in Poland is characterized by such attitudes as honour, steadfastness, the "might is right" principle, and moral and economic conservatism. Supporters tend to sympathize with political parties embracing right-wing values. The article points out important elements of Polish history that could have affected the ideological construction of the supporters' vision. In the absence of historical civic and left-wing tradition, Polish supporters emerged during the period of the country's struggle for freedom as a community structured by militant, conservative, punitive, and masculine frames of reference. Since the values of a particular group cannot be analysed without an assessment of its broader cultural and social context, the article also presents the different dimensions of Polish history and society in order to provide a contextual background influencing fandom.